Histological, morphometric, protein and gene expression analyses of rat retinas with ischaemia–reperfusion injury model treated with sildenafil citrate. Issue 3 (June 2017) - Zanoni, Diogo S.; Da Silva, Germana A.; Ezra‐Elia, Raaya; Carvalho, Márcio; Quitzan, Juliany G.; Ofri, Ron; Laus, José L.; Laufer‐Amorim, Renee
Abstract : Summary: The aim of this study was to better understand the role of apoptosis in a retinal ischaemia–reperfusion injury model and to determine whether sildenafil citrate treatment can prevent retinal cell apoptosis. Thirty‐six rats were divided into a control group ( n  =   6) and two experimentally induced ischaemia–reperfusion groups (7 and 21 days; n  =   15 per group). The induced ischaemia–reperfusion groups were treated with sildenafil for 7 and 21 days ( n  =   10 per group), and 10 animals were treated with a placebo for the same period ( n  =   5 per group). Paracentesis of the anterior chamber was performed with a 30‐G needle attached to a saline solution (0.9%) bag positioned at a height of 150 cm above the eye for 60 min. Intraocular pressure was measured by rebound tonometer (TonoVet ® ). The eyes were analysed by histology and morphometry, and by immunohistochemistry and qRT‐PCR for expression of Caspase‐7, Caspase‐6, Caspase‐9, Tnf‐r2, Fas‐l, Bcl‐2 and Bax . Sildenafil‐treated animals showed lower levels of histopathological changes (inflammatory, cellular and tissue) than their placebo‐treated counterparts at both 7 and 21 days. The retinal ganglion cell layer (RGC) was preserved in the sildenafil groups (SG), with a cell count closer to control than in the placebo groups (PG). Caspase‐7 expression was significantly higher in both treated groups at 7 days compared to controls. Gene expression levels in both treatment groups differed from the controls, but in SG Bax and Caspase‐6 expression levels were similar to control animals. These results suggest that the main mechanism of retinal cell death in this model is apoptosis, as there is an increase in pro‐apoptotic factors and decrease in the anti‐apoptotic ones. Also, sildenafil seems to protect the retinal ganglion cell layer from apoptosis. Cell survival was evident in the histological and morphometric analyses, and sildenafil treatment had a protective effect in the apoptosis pathways, with gene expression levels in SG similar to the controls.